Evaluation of Drug-Related Receptors in Children With Dilated Cardiomyopathy - Guo, Qing; Liu, Jie; Zhu, Peng; Liu, Yali; Dong, Nianguo; Shi, Jiawei; Peng, Hua (Frontiers in Pediatrics, 2019)
Background-Effective therapeutic strategies for dilated cardiomyopathy in children are limited. The current treatment for children presenting with dilated cardiomyopathy (DCM) consists mainly of supportive failing heart (HF) therapy. While the medicine for children with DCM is generally the same as adult DCM patient, there is the lack of sufficient randomized prospective studies on the clinical efficacy in pediatric DCM. We explored the appropriate medicine for children patients. Methods-Ultrastructure of pediatric and control hearts were analyzed by electron microscopy and HE staining. Left ventricular tissue from children DCM and control group were subjected to quantitative RT-PCR (qRT-PCR) to study the expression of mRNAs of corresponding receptors of medicine, involving renin-angiotensin-aldosterone system (RAAS) system, digaoxin, milrinone, and β-receptor blockers, in clinic for children patients. Further, the differences in drug receptors in heart tissue between children and adults DCM were analyzed. Result-Compared with control, children DCM group showed marked abnormalities in structure and organelles. The mRNA expression of prorenin receptor (PRR), angiotensin-converting enzyme (ACE), REN, NEP, ATP1A1 and phosphodiesterase3 (PDE3A) were higher in children DCM group. Interestingly, the mRNA expression of these medicine receptors were much higher in children group than adult group. Conclusion-ACE inhibitor, PRR or REN receptor inhibitors, PDE3 inhibitor and LCZ696 may be effective in children with DCM. While the β-receptor blockers are not valid in pediatric DCM. Moreover, the expression of receptors is much abundant in children. These data will improve the correct choice of drugs for the DCM patient and speed up treatment, enhance survival rate.